2004
DOI: 10.1103/physrevb.70.125304
|View full text |Cite
|
Sign up to set email alerts
|

SU(4)skyrmions and activation energy anomaly in bilayer quantum Hall systems

Abstract: The bilayer quantum Hall (QH) system has four energy levels in the lowest Landau level, corresponding to the layer and spin degrees of freedom. We investigate the system in the regime where all four levels are nearly degenerate and equally active. The underlying group structure is SU͑4͒. At = 1 the QH state is a chargetransferable state between the two layers and the SU͑4͒ isospin coherence develops spontaneously. Quasiparticles are isospin textures to be identified with SU͑4͒ skyrmions. The skyrmion energy co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Since the spin degree of freedom is not frozen in CF liquids, these theories may provide an important clue. Another possibility may be an excitation including both spin and pseudospin [23]. Further discussion on this issue, however, is beyond the scope of this Letter.…”
mentioning
confidence: 99%
“…Since the spin degree of freedom is not frozen in CF liquids, these theories may provide an important clue. Another possibility may be an excitation including both spin and pseudospin [23]. Further discussion on this issue, however, is beyond the scope of this Letter.…”
mentioning
confidence: 99%
“…The SU(N ) extension of the magnetic translation group, T M × SU(N ), with N ≥ 4, was indeed the starting point of several other theoretical works on bilayer quantum Hall systems. 22,23,28,29 We have thus shown that a SU(4) description of the texture states is necessary even if the ground state has the reduced internal symmetry SU(2)×SU(2).…”
Section: Discussionmentioning
confidence: 98%
“…The energetics of the resulting topological excitations has been an active field of study in recent years. 25,26,27,28,29,30,31 In this paper, we consider the properties of SU(2)×SU(2) Skyrmions in the presence of realistic anisotropy terms. We do this from a perspective of entanglement between the spin and pseudospin degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…What are observed experimentally are the classical densities, which are expectation values such as ρ cl (p) = ⟨S|ρ(p)|S⟩, where |S⟩ represents a generic state in the LLL. The SU(4) effective Hamiltonian density are given by [3] …”
Section: The Su(4) Effective Hamiltonian and The Ground State Structurementioning
confidence: 99%
“…The ground state structure of the ν = 2 bilayer QH system has been investigated based on the SU(4) formalism [3,4]. However, the effective Hamiltonian for the Goldstone modes has not been derived, especially in the CAF phase.…”
Section: Introductionmentioning
confidence: 99%